THE ROLE OF LANGUAGE IN SHAPING SOCIAL IDENTITY AND CULTURAL AWARENESS - Sayitova Sevinch Abdurasulovna (Western European Studies, 2026)
Language is one of the most profound tools humans have for constructing and communicating meaning in their lives. It is not simply a method for exchanging information, but a fundamental instrument in the development of individual and collective identities within society. The role of language goes far beyond its grammatical and structural dimensions; it acts as the bedrock upon which our perceptions, beliefs, and notions about ourselves and others are built. Through language, individuals are able to express their membership to various social groups, share their heritage, establish their values, and foster a sense of belonging that extends to both local and global communities.
Keywords: language; social identity; cultural awareness